Productivity and quality of sweet potato roots cultivation with and without chicken manure - Steffler, Andersson Daniel (2022)
Sweet potato (Ipomoea batatas) has cultural, social and economic importance due to its rusticity and wide climate adaptation, being cultivated in Brazil for human and animal food. However, cultivation is carried out mainly without fertilization and with Creole cultivars. The objective was to evaluate the yield and quality of roots of sweet potato cultivars with and without fertilization of chicken manure in an Oxisol. The experiment was carried out under field conditions in the 2015/16 and 2016/17 seasons in a randomized block design with three replications in 6 m2 plots. Four sweet potato cultivars, BRS Rubissol, BRS Amélia, BRS Cuia and Crioula, were used. Root productivity, number, length and diameter of roots, and cracked roots were evaluated. In both cultivation conditions, the virus-free cultivars Rubissol, Amélia and Cuia showed higher average root yields, 43,941, 45,498 and 52,095 kg ha-1, respectively, compared to the Crioula cultivar with 3,389 kg ha-1. Fertilization with chicken manure does not increase the productivity, number, length and diameter of roots, but it does increase the number of cracked roots. The cultivation of virus-free sweet potato without fertilizer reduces cracked roots by an average of 51.4%.